AN EXTENSIVE REVIEW OF VIBRATION METHODS FOR BONE HEALING ASSESSMENT (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
The present study offers a thorough examination of the utilization of vibration techniques in the evaluation of bone healing in the domain of orthopedics and rehabilitation. In addition to providing critical insights into the mechanical properties of healing bones and their influence on treatment choices, the review includes an investigation of objective, non-invasive techniques for tracking the advancement of bone healing. The study also explores the function of vibration-based assessment methods in treatment planning and how they support ongoing research and development initiatives. Additionally, the development of this important field is clarified by discussing the historical background and current bone mechanics research initiatives. The goal of the review is to present a comprehensive understanding of vibration methods for assessing bone healing and their possible applications in clinical practice and research. The outcomes of this review state that the non-invasive techniques help clinicians make well-informed treatment decisions by offering insightful information about bone mechanics. In addition, the review highlights the potential influence of vibration methods on clinical practice and research, indicating potential for improving orthopedic care